Embodied Cognition in Performance: The Impact of Michael Chekhov’s Acting Exercises on Affect and Height Perception - Olenina, Ana Hedberg; Amazeen, Eric L.; Eckard, Bonnie; Papenfuss, Jason (Frontiers in Psychology, 2019)
Modern embodied approaches to cognitive science overlap with ideas long explored in theater. Performance coaches such as Michael Chekhov have emphasized proprioceptive awareness of movement as a path to attaining psychological states relevant for embodying characters and inhabiting fictional spaces. Yet, the psychology of performance remains scientifically understudied. Experiments, presented in this paper, investigated the effects of three sets of exercises adapted from Chekhov’s influential techniques for actors’ training. Following a continuous physical demonstration and verbal prompts by the actress Bonnie Eckard, 29 participants enacted neutral, expanding, and contracting gestures and attitudes in space. After each set of exercises, the participants’ affect (pleasantness and arousal) and self-perceptions of height were measured. Within the limitations of the study, we measured a significant impact of the exercises on affect: pleasantness increased by 50% after 15 min of expanding exercises and arousal increased by 15% after 15 min of contracting exercises, each relative to the other exercise. Although the exercises produced statistically non-significant changes in the perceived height, there was a significant relation between perceived height and affect, in which perceived height increased with increases in either pleasantness, or arousal. These findings provide a preliminary support for Chekhov’s intuition that expanding and contracting physical actions exert opposite effects on the practitioners’ psychological experience. Further studies are needed to consider a wider range of factors at work in Chekhov’s method and the embodied experience of acting in general.